I speak fast when I move fast: the speed of illusory self-motion (vection) modulates the speed of utterances - Seno, Takeharu; Ihaya, Keiko; Yamada, Yuki (Frontiers in Psychology, 2013)
Speed of utterance is an important factor in smooth and efficient conversation. We report a technique to increase utterance speed and that might improve a speaker’s impression and information efficiency in conversation. We used a visual display consisting of optic flows in a large visual field that induced participants’ illusory self-motion perception (vection). The speed of vection corresponded to the speed of the optic flows. Using this method, we investigated whether vection speed affects utterance speed. We presented fast- and slow-moving optic flow stimuli while dynamically swapping random dots presented to participants, during which time the participants were asked to talk for two minutes. Results revealed that the utterance speed was significantly faster in the fast optic flow condition.